2010
DOI: 10.1007/s11540-010-9151-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of Solanum dulcamara L. in Potato Late Blight Epidemiology

Abstract: Four sites with naturally growing Solanum dulcamara were surveyed during 2006 and 2007 for the presence of late blight. Despite 2 years of observations, no late blight was detected among natural populations of bittersweet. Nevertheless, repeated infections occurred on few S. dulcamara plants from a collection growing in a botanical garden in the same years. These plants were used to investigate the possibility of survival of the inoculum between seasons. In the respective years, a set of 21 and 52 S. dulcamara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The goal of this study was to identify new genetic factors responsible for the resistance against P. infestans observed in S. dulcamara accessions (Golas et al 2010b). Results published by Golas et al (2010a), indicated the possibility that Rpi gene(s) other than Rpi-dlc1 might be present in S. dulcamara.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of this study was to identify new genetic factors responsible for the resistance against P. infestans observed in S. dulcamara accessions (Golas et al 2010b). Results published by Golas et al (2010a), indicated the possibility that Rpi gene(s) other than Rpi-dlc1 might be present in S. dulcamara.…”
Section: Discussionmentioning
confidence: 99%
“…Late blight, is one of the most serious potato diseases worldwide [ 14 ]. However, it was shown that bittersweet has a minimal role in late blight infections since most plants are resistant and the inocula of the pathogen do not overwinter [ 15 ]. Populations of this species seem to have experienced a genetic bottleneck [ 16 ], but some allelic variation was found to be distributed among populations resulting in more structured populations at larger regional levels [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…de Bary, a dangerous oomycete that is the causal agent of late blight (Janse, 1996). However, recent studies suggest that bittersweet may not play a key role in late blight epidemiology as it does not serve as a reservoir of inocula overwintering from the previous season (Golas et al , 2010 a ). Late blight ranks as economically the most important disease of potato and tomato.…”
Section: Introductionmentioning
confidence: 99%